Evaluation of Host Cell Impurity Effects on the Performance of Sterile Filtration Processes for Therapeutic Viruses - Evan Wright; Karina Kawka; Maria Fe C. Medina; David R. Latulippe (Membranes, 2022)
Efficient downstream processing represents a significant challenge in the rapidly developing field of therapeutic viruses. While it is known that the terminal sterile filtration step can be a major cause of product loss, there is little known about the effect of host cell impurities (DNA and protein) on filtration performance. In this study, fractions of relatively pure Vero host cell protein and DNA were spiked into a highly pure preparation of vesicular stomatitis virus (VSV). Then, the resulting solutions were sterile filtered using two commercially available 0.22 µm rated microfiltration membranes. A combination of transmembrane pressure measurements, virus recovery measurements, and post-filtration microscopy images of the microfiltration membranes was used to evaluate the sterile filtration performance. It was found that increasing the amount of host cell protein from approximately 1 µg/mL (in the un-spiked VSV preparation) to 25 µg/mL resulted in a greater extent of membrane fouling, causing the VSV recovery to decrease from 89% to 65% in experiments conducted with the highly asymmetric Express PLUS PES membrane and to go as low as 48% in experiments conducted with the symmetric Durapore PVDF membrane. Similar effects were not seen when bovine serum albumin, a common model protein used in filtration studies, was spiked into the VSV preparation, which indicates that the sterile filtration performance is critically dependent on the complex composition of the mixture of host cell proteins rather than the presence of any protein. The results presented in this work provide important insights into the role of host cell impurities on the performance of sterile filtration processes for therapeutic viruses.